2017
DOI: 10.1158/1538-7445.sabcs16-p4-22-13
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P4-22-13: Everolimus plus trastuzumab and paclitaxel as first-line therapy in women with HER2+ advanced breast cancer: Overall survival results from BOLERO-1

Abstract: Background Everolimus (EVE), an mTOR inhibitor has shown activity in HER2+ advanced breast cancer (ABC) in both preclinical and clinical studies. In the pivotal BOLERO-1 trial (NCT00876395), the progression-free survival (PFS) was not significantly different between the EVE + trastuzumab (TRAS) + paclitaxel (PAC) combination and placebo (PBO) + TRAS + PAC in the full HER2+ population (EVE, 15.0 mo vs PBO, 14.5 mo; HR=0.89; 95% CI: 0.73-1.08; p=0.1166). Although not reaching protocol defined leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The MARIANNE trial, a three-arm study, reported the PFS or OS,27,28 while the other trials were two-arm studies. Seven publications have explicitly reported the data both PFS and OS in one study,8,13,15,2932 and the other six publications only mention one of the two indicators 912,27,28. The ORR and common AEs (hematologic toxicity and cardiac safety) were abstracted from the publications included.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The MARIANNE trial, a three-arm study, reported the PFS or OS,27,28 while the other trials were two-arm studies. Seven publications have explicitly reported the data both PFS and OS in one study,8,13,15,2932 and the other six publications only mention one of the two indicators 912,27,28. The ORR and common AEs (hematologic toxicity and cardiac safety) were abstracted from the publications included.…”
Section: Resultsmentioning
confidence: 99%
“…Other dual anti-HER2 regimens, ETP and T-DM1+Pzmb, were also used to treat MBC but with no satisfactory result. There were no statistical differences in the PFS, OS, and ORR regarding the standard TP regimen (trastuzumab and taxane) for MBC, although the hormone receptor status of patients had an effect 12. T-DM1 is recommended as a second-line or further-line treatment 37…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, it showed less encouraging results in two large phase III trials in HER2-positive MBC (BOLERO-1 and BOLERO-3). BOLERO-1, which studied addition of everolimus to trastuzumab + taxanes in first line metastatic treatment, reported that everolimus was associated with increased toxicity without any improvement in either PFS or OS ( 129 , 130 ). BOLERO-3 tested addition of everolimus to trastuzumab + vinorelbine in second line metastatic treatment for patients previously exposed to trastuzumab and taxanes.…”
Section: Therapies Under Developmentmentioning
confidence: 99%